Pengaruh Model Tipe Team Assisted Individualization (TAI) Terhadap Hasil Belajar Siswa pada Pembelajaran Pendidikan Pancasila di Kelas IV SD - Nurul Ikhsani Putri; Monica Puspa Cahyani; Adrias Adrias; Nur Azmi Alwi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The research aims to determine the effect of the Team Assisted Individualization learning model on student learning outcomes in Pancasila education learning in class IV SDN 22 Duku. This research uses a quantitative type of research with a quasi-experimental design experimental method in the form of a non-equivalent control group. The sample in this study was all 34 class IV students at SDN 22 Duku, of which 17 class IV A students and 17 class IVB students. The experimental class in this research is class IV A and the control class is class IV B. Based on the data analysis that has been carried out, the t count is 3.18 and the t table is 2.042. so the experimental class in this study was class IV A and the control class was class IV B. This shows that there is a significant influence on the implementation of the Team Assisted Individualization (TAI) type cooperative model on the results of dozens of class IV elementary school students.